Determinants Affecting Growth Of Islamic Bank Assets In Indonesia: External Factors As Moderating Variables - Priyono Puji Prasetyo Priyono; Agus Susetyohadi Agus (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Introduction to The Problem: Internal and external factors will affect the growth of an industry, including the Islamic banking industry. Both can measure Islamic banks' growth more broadly and deeply.. Purpose: This study aims to analyze the relationship of internal factors to the growth of Islamic bank assets in Indonesia: external factors as moderating variables. Methodology: To answer the objectives of this study, secondary data in the form of panel financial reports for the period 2012-2021 were used. The samples taken in this study were 12 Islamic Commercial Banks (BUS), 21 Islamic Business Units (UUS), and 164 Islamic BPRs. Internal factors include CAR, FDR, NPF, and DPK, and the external factor used is the BI Rate. These financial data were then tested using the panel data regression analysis method through the Moderated Regression Analysis (MRA) estimation model with the help of the SPSS 25 statistical tool. Findings: The results showed that the BI Rate variable increased the relationship of internal variables to the growth of Islamic bank assets.